Antibiotic Residues and Resistance in Three Wastewater Treatment Plants in Romania - Svetlana Iuliana Polianciuc; Alexandra Ciorîță; Maria Loredana Soran; Ildiko Lung; Béla Kiss; Maria Georgia Ștefan; Daniel Corneliu Leucuța; Anca Elena Gurzău; Rahela Carpa; Liora Mihaela Colobațiu; Felicia Loghin (Antibiotics, 2024)
This study evaluates antibiotic residues and bacterial loads in influent and effluent samples from three wastewater treatment plants (WWTPs) in Romania, across four seasons from 2021 to 2022. Analytical methods included solid-phase extraction and high-performance liquid chromatography (HPLC) to quantify antibiotic concentrations, while microbiological assays estimated bacterial loads and assessed antibiotic resistance patterns. Statistical analyses explored the impact of environmental factors such as temperature and rainfall on antibiotic levels. The results showed significant seasonal variations, with higher antibiotic concentrations in warmer seasons. Antibiotic removal efficiency varied among WWTPs, with some antibiotics being effectively removed and others persisting in the effluent, posing high environmental risks and potential for antibiotic resistance development. Bacterial loads were higher in spring and summer, correlating with increased temperatures. Eight bacterial strains were isolated, with higher resistance during warmer seasons, particularly to amoxicillin and clarithromycin.